Rescate, habilitación, y puesta en marcha del filtro prensa de alta presión y alta temperatura (hpht filter press) para el laboratorío de petróleos de la fict-ESPOL - Núñez Garcés, Carlos Francisco (2010)
Filter Presses are commonly used to test and evaluate the filtration properties of drilling fluids, cement slurries, and treatment of fluids to formation cores. HPHT Filter Presses provide an efficient mean to evaluate these properties under high temperature and high pressure, simulating bottom hole conditions. The objective of this document is to rescue, habilitate, and run the HPHT Filter Press for the Petroleum Laboratory at the Department of Earth Science Engineering at the Escuela Superior Politécnica del Litoral, and furthermore, illustrate the reader about a complete and correct use of the equipment. This document presents references about the device general description, classification, importance and general characteristics. Through the pages of this document it is shown the initial conditions in which the device was found in the first place, giving accurate detail of the fundamental parts and its components. This thesis details the procedures of improvement to the HPHT Filter Press, conditioning and detailed analysis, along with the lab testing performed to proof its efficiency.